In situ measurement of VUV/UV radiation from low-pressure microwave-produced plasma in Ar/O2 gas mixtures. (17th July 2017) - Iglesias, E J; Mitschker, F; Fiebrandt, M; Bibinov, N; Awakowicz, P
Abstract: Ultraviolet (UV) and vacuum ultraviolet (VUV) spectral irradiance is determined in low-pressure microwave-produced plasma, which is regularly used for polymer surface treatment. The re-emitted fluorescence in the UV/VIS spectral range from a sodium salicylate layer is measured. This fluorescence is related to VUV/UV radiation in different spectral bands based on cut-off filters. The background produced by direct emitted radiation in the fluorescence spectral region is quantified using a specific background filter, thus enabling the use of the whole fluorescence spectral range. A novel procedure is applied to determine the absolute value of the VUV/UV irradiance on a substrate. For that, an independent measurement of the absolute spectral emissivity of the plasma in the UV is performed. The measured irradiances on a substrate from a 25 Pa Ar/O2 -produced plasma are in the range of 10 15 –10 16 ( p h o t o n s − 1 c m − 2 ) . These values include the contribution from impurities present in the discharge.